DISCRIMINATION OF GENDER AGAINST WOMEN IN THE NOVEL KIM JI-YOUNG, BORN 1982 BY CHO NAM-JOO - Nada Firdaus; Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2022)
Sex-based discrimination includes gender discrimination. The fundamental cause of gender discrimination against women is that patriarchal ideology shapes society’s attitudes and behaviors. This study examines how women are treated differently because of their gender in the novel Kim Ji-Young, Born 1982. This study aims to find out the types and impacts of gender discrimination against women in the novel. This study is categorized as qualitative research and uses a feminism approach. The feminism theory presented in Simone de Beauvoir’s book The Second Sex (1949) is used by the researcher to analyze the novel. The researcher discovered two types of gender discrimination in Kim Ji-Young, Born 1982; gender discrimination in domestic spaces and gender discrimination in public spaces. The five different forms of gender discrimination in domestic spaces are; (1) the expectation that women should have male offspring, (2) the favoritism toward sons over daughters, (3) the idea that sons are the ones who ensure the success of the family, (4) woman as a reproducer, and (5) woman as a housewife. The novel also shows three forms of gender discrimination in public spaces; (1) discrimination toward women in school, (2) discrimination toward women in the workplace, and (3) sexual harassment of women. Furthermore, the main character, Kim Ji-Young, experiences gender discrimination against women, and the impacts of the gender discrimination on Kim Ji-Young are feeling inferior and experiencing mental changes. Keywords: gender discrimination, feminism, patriarchy ideology, novel